2015
DOI: 10.15446/ing.investig.v35n1sup.53698
|View full text |Cite
|
Sign up to set email alerts
|

Power system reliability impacts of wind generation and operational reserve requirements

Abstract: Due to its variability, wind generation integration presents a significant challenge to power system operators in order to maintain adequate reliability levels while ensuring least cost operation. This paper explores the trade-off between the benefits associated to a higher wind penetration and the additional operational reserve requirements that they impose. Such exploration is valued in terms of its effect on power system reliability, measured as an amount of unserved energy. The paper also focuses on how ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The operating impact of wind-power generation, as well as the corresponding additional grid-balancing requirements, have been studied widely [8][9][10][11]. The report in Reference [12] concluded that the impact of wind-power variability is relatively small in the regulation time scale (minutes), larger during the load-following time scale (minutes to hours), and more significant for the unit commitment/scheduling time scale (day).…”
Section: Introductionmentioning
confidence: 99%
“…The operating impact of wind-power generation, as well as the corresponding additional grid-balancing requirements, have been studied widely [8][9][10][11]. The report in Reference [12] concluded that the impact of wind-power variability is relatively small in the regulation time scale (minutes), larger during the load-following time scale (minutes to hours), and more significant for the unit commitment/scheduling time scale (day).…”
Section: Introductionmentioning
confidence: 99%